Sistem Pengarsipan Data Pegawai Menggunakan Metode Mixturemodelling Berbasis Web - Yulia Darmi; Septedy Prasetya Dwi Chandra; Diana Diana; Pahrizal Pahrizal (Jurnal Media Infotama, 2023)
Technological developments are increasing very fast along withcurrent development. It encourages every human being, especially tatabusiness as a provider of information to continuously follow developments and make decisions to improve,develop, and update any information presented to provide good service. The general section is part of the institution that is authorized to handle documents andfiling. In the General Section, verything related to archiving documents is archived and updated. The use of Microsoft Excel to handle documents in the General Section raises obstacles which include difficulties in searching for old data, formats in the documentation process that are still inconsistent, and difficulty knowing which documents will be processed. Therefore the researchers conducted this research aiming to produce an application that is able to manage document data so that managing document data is easier. From the research that the writer is doing, it will produce an application using the PHP programming language and SQL Server as the database, where the user of the application is the user. With this application, it can help users in the process of documenting, filing, and preparing document reports. The application can also be a solution in managing, storing, and archiving documents.